1998
DOI: 10.1007/bf02499168
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of hypophysial adrenocortical system in rats selected by the threshold of sensitivity to electrical current

Abstract: An enhancement of stress reactivity of the hypophysial-adrenocortical system in response to emotional and physical influence was shown in rats with a low threshold of sensitivity to electrical current. This phenomenon was observed as a rise in the maximum level of blood corticosterone and acceleration of stressor hormonal response. In the high-threshold rats a decrease in sensitivity of the hypophysial adrenocortical system to the feedback signals was observed. Key Words: hypophysial adrenocortical system; str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It is known that subcutaneous administration of corticosterone in mice for 14 days leads to hyperactivity of the amygdala, as well as to disturbances of amygdala-mediated memory of a traumatic event [29]. Previously, it was shown that strains of highly excitable rats with a low threshold of sensitivity to electric current are characterized by increased stress reactivity of the HPA, accelerated development of the hormonal response, and reduced sensitivity of the HPA to feedback signals [30]. It makes animals of this strain more susceptible to immune dysfunctions in response to chronic stress and may lead to excessive activation of the amygdala.…”
Section: Plos Onementioning
confidence: 99%
“…It is known that subcutaneous administration of corticosterone in mice for 14 days leads to hyperactivity of the amygdala, as well as to disturbances of amygdala-mediated memory of a traumatic event [29]. Previously, it was shown that strains of highly excitable rats with a low threshold of sensitivity to electric current are characterized by increased stress reactivity of the HPA, accelerated development of the hormonal response, and reduced sensitivity of the HPA to feedback signals [30]. It makes animals of this strain more susceptible to immune dysfunctions in response to chronic stress and may lead to excessive activation of the amygdala.…”
Section: Plos Onementioning
confidence: 99%
“…Presumably, LT rats are more sensitive to genotoxic action due to the selection in favor of a low nerve excitability threshold, which is somehow connected with the genome response to stress in cells of different brain structures. Previously, it was shown that LT rats are characterized by increased stress reactivity of the HPA, accelerated development of the hormonal response, and reduced sensitivity of the HPA to feedback signals (Ordyan et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Stress experienced by mothers during various terms of gestation can have a negative impact on physiological functions in their progeny [10], but biochemical mechanisms of these disorders are still unclear. On the one hand, we know the important role of the psychotype in the development of pathological reaction to stress [2,[5][6][7]. Study of biochemical processes in animals with genetically determined differences in the CNS function will help to understand the mechanisms and regularities in the formation of pathological states.…”
mentioning
confidence: 99%
“…Study of biochemical processes in animals with genetically determined differences in the CNS function will help to understand the mechanisms and regularities in the formation of pathological states. Rats with high and low excitability threshold (HET and LET, respectively) selected at I. P. Pavlov Institute of Physiology are models of opposite types of the nervous system functioning [6].…”
mentioning
confidence: 99%